Le bon fonctionnement des finances internationales, la promotion des accords de confirmation du FMI et la redaction des accords de pret prives. (Pamphlet Series, 1982)
This paper discusses the promotion of IMF Stand-By Arrangements (SBAs), the drafting of private loan agreements, and order in international finance. The IMF approves a SBA or an extended arrangement for the benefit of a member country of the IMF only if the member presents to the IMF a letter of intent in which it sets forth a program of financial and economic adjustment that is likely to solve a present, or to fend off a possible balance-of-payments or reserve problem. A purchase is made in return for the purchasing member's currency. An extended arrangement is a variant that is in use for the purposes of a particular policy of the IMF.